After five years' application of the European Union monitoring, reporting, and verification (MRV) mechanism: review and prospectives - Luo, Xi (2024)
The global shipping sector is a major generator of greenhouse gas (GHG) emissions. In 2018, to reduce emissions, the European Union (EU) implemented a monitoring, reporting, and verification (MRV) system for large ships using EU ports. The MRV system has been functional for five years, with four years of data available as of May 2023. Despite this, the MRV data have not been fully explored, particularly in terms of analyzing the temporal trends of key parameters in MRV reports and evaluating the emission performance of shipping companies during the MRV implementation period. To address these gaps, this study analyzes MRV data collected from 2018 to 2021, investigating trends in ship's basic information, emissions monitoring methods, and energy efficiency. A case study of five shipping companies is conducted to evaluate their carbon emission performance, which highlights the impact of the coronavirus disease 2019 (COVID-19) pandemic on the industry. Furthermore, this study proposes policy recommendations and management strategies based on the data analysis results; these include facilitating collaboration and knowledge sharing, investing in green shipping infrastructure, and adopting accurate monitoring methods. These recommendations can guide policymakers and industry stakeholders to improve the MRV system and promote a more sustainable shipping industry in the EU and worldwide.